The Effect of Decisional Leader Procrastination on Employee Innovation: Investigating the Moderating Role of Employees' Resistance to Change. (February 2022) - Haesevoets, Tessa; De Cremer, David; Hirst, Giles; De Schutter, Leander; Stouten, Jeroen; van Dijke, Marius; Van Hiel, Alain
Most prior research has examined procrastination as a type of self -defeating behavior. The present research, however, focused on the social consequences of procrastination, by investigating how decisional leader procrastination as a leader trait affects others in the workplace. We specifically developed the argument that the way in which employees deal with changes plays a critical moderating role in the relationship between leader procrastination and employee innovation. More precisely, we hypothesized that decisional leader procrastination negatively impacts employee innovation, but only so for employees who are low (compared to high ) in resistance to change. This prediction was tested in an experimental study (Study 1) and two double-source survey studies (Studies 2 and 3). In support of our prediction, the results showed that an indecisive leader indeed undermines the innovation of those employees who embrace—rather than resist—changes. Critically, however, our findings also illustrated that when being supervised by a decisive leader, these particular employees are actually most likely to bring forward the process of innovation. Theoretical and practical implications of our results are discussed.